Suitability of compensatory saltmarsh habitat for feeding and diet of multiple estuarine fish species - Thomas Stamp; Elizabeth West; Steve Colclough; Shaun Plenty; Benjamin Ciotti; Tim Robbins; Emma Sheehan (Fisheries Management and Ecology, 2023)
Saltmarsh provides essential fish feeding and nursery habitat but has globally declined by 50%. We used a statistical block design to compare fish feeding activity within human‐engineered or “re‐aligned” saltmarsh to established saltmarsh. Linear and multivariate modelling highlighted that Thinlip Mullet ( Chelon ramada ) and European Bass ( Dicentrarchus labrax ) feeding rates were 16% and 31% lower within re‐aligned than established saltmarshes, whereas Gobies ( Pomatoschistus spp.) fed at the same rate as in both habitats. Analysis of European bass and Goby gut contents highlighted that important detritivorous prey species were up to 85.6% lower in re‐aligned sites. Lower vegetation density may have negatively affected the feeding ecologies of fishes within re‐aligned sites. However, due to the ecological value and potential for further improvement or habitat development, continued assessment of the beneficial effects of re‐aligned sites for fisheries and net gain perspectives is needed.

Hive‐stored pollen of honey bees: many lines of evidence are consistent with pollen preservation, not nutrient conversion - Kirk E. Anderson; Mark J. Carroll; Tim Sheehan; Brendon M. Mott; Patrick Maes; Vanessa Corby‐Harris (Molecular Ecology, 2014)
Honey bee hives are filled with stored pollen, honey, plant resins and wax, all antimicrobial to differing degrees. Stored pollen is the nutritionally rich currency used for colony growth and consists of 40–50% simple sugars. Many studies speculate that prior to consumption by bees, stored pollen undergoes long‐term nutrient conversion, becoming more nutritious ‘bee bread’ as microbes predigest the pollen. We quantified both structural and functional aspects associated with this hypothesis using behavioural assays, bacterial plate counts, microscopy and 454 amplicon sequencing of the 16S rRNA gene from both newly collected and hive‐stored pollen. We found that bees preferentially consume fresh pollen stored for 96 h. The estimated microbe to pollen grain surface area ratio was 1:1 000 000 indicating a negligible effect of microbial metabolism on hive‐stored pollen. Consistent with these findings, hive‐stored pollen grains did not appear compromised according to microscopy. Based on year round 454 amplicon sequencing, bacterial communities of newly collected and hive‐stored pollen did not differ, indicating the lack of an emergent microbial community co‐evolved to digest stored pollen. In accord with previous culturing and 16S cloning, acid resistant and osmotolerant bacteria like Lactobacillus kunkeei were found in greatest abundance in stored pollen, consistent with the harsh character of this microenvironment. We conclude that stored pollen is not evolved for microbially mediated nutrient conversion, but is a preservative environment due primarily to added honey, nectar, bee secretions and properties of pollen itself.